The effect of Ni3(Cr0.2W0.4Ti0.4) particles with DO22 structure on the deformation mode and mechanical properties of the aged Ni-Cr-W-Ti alloy. (August 2018) - Gao, Xiangyu; Hu, Rui; Yang, Jieren
Abstract: It has been found that the DO22 Ni3 (Cr0.2 W0.4 Ti0.4 ) particles play a dominant role in improving the strength of the aged Ni-Cr-W-Ti superalloy. The precipitation of DO22 phase also changed the preferred deformation mode from slip in the as-solutionized alloy into twinning in the aged alloy. Strengthening of the aged superalloy has been determined to be based on shearing mechanism to achieve high cutting stress which is required for partial dislocations to cut through coherent DO22 precipitates and thus produce plastic deformation, resulting in a dramatic increase in yield strength of the aged superalloy. Graphical abstract: Unlabelled Image